الرثاء النسوي وتمثلاته في النص المسرحي العربي المعاصر: مسرحية الخنساء اختيارا - العبادي، نزار شبيب كريم; هاشم، زينب نوري (جامعة بغداد - كلية الفنون الجميلة, 2020)
يتناول البحث الرثاء النسوي وتمثلاته في النص المسرحي العربي المعاصر بوصفه من أغراض الشعر العربي وتطورت صوره ونماذجه ودواعيه وتعددت بواعثه عبر فترات زمانية مختلفة وتجسدت به صورة درامية وتمثلات تناغمت مع فن المسرح ولأجل تسليط الضوء على تلك التمثلات جاءت هذه الدراسة للبحث عن تمثلات ظاهرة الرثاء في نصوص المسرح العربي وقد تضمن هذه الدراسة مقدمة البحث التي عرض فيها الباحثان مشكلة البحث وأهميته وهدفه. ثم الإطار النظري الذي تناول تأسيساً نظرياً للبحث اشتمل على مبحثين هما: الرثاء النسوي نظرة تاريخية والثاني: الرثاء في المسرح وخرج الباحثان بمجموعة من المؤشرات اعتمداها في تحليل نموذج عينة البحث والتي تحددت بمسرحية (الخنساء) للكاتب (محمد الصالح رمضان) والتي تتوافق مع هدف البحث. وبعد التحليل خرج الباحثان بمجموعة نتائج منها: تمثلت أغلب مراثي الخنساء في ندب الموتى والنواح عليهم وجسدتها من خلال صورة الحزن والأسى.
The research addresses the feminist lament and its representations in the contemporary Arab theatrical text as one of the purposes of the Arabic poetry and its images, samples, and reasons developed and its incentives multiplied through different time periods in which a dramatic image and representations have been manifested that harmonized with the art of theatre. In order to shed light on these representations, this stud)/ has come to look for the representations of lament phenomenon in the Arab theatre texts. The study consists of an introduction in which the two researchers put forward the research problem, significance and objectives, and a theoretical framework which tackles a theoretical foundation for the research consisting of two sections: the feminist lament a historical view and the second section: lament in the theatre. The two researchers came up with a set of indicators adopted in the analysis of the research sample which was determined by (Al-Khansaa) play by the writer (Mohamed Saleh Ramadan) which agrees with the research objective. After the analysis, the researchers reached at a set of results among them: most of Al-Khansaa' lament is represented by mourning the dead and embodying them through images of sadness and grief.
Keywords: الأدب العربي -- الرثاء النسوي -- النصوص المسرحية -- الفكر المعاصر